A fast heuristic for a lot splitting and scheduling problem of a textile industry - Pimentel, Carina (2012)
In this paper we address a lot splitting and scheduling problem of a Textile factory that produces garment pieces. Each garment piece is made of a set of components that are produced on the knitting section of the company. The problem consists of finding a weekly production plan for the knitting section, establishing the quantities to produce of each component (organized in one or several lots), and where and when starting/completion times) to produce them. The main contribution of this work is the development of a constructive heuristic that generates automated knitting scheduling plans. The heuristic produces solutions very fast for a set of randomly generated instances based on real world data.